Controlled Retention and Release of Biomolecular Transport Systems Using Shape‐Changing Polymer Bilayers. Issue 52 (24th November 2016) - Stoychev, Georgi; Reuther, Cordula; Diez, Stefan; Ionov, Leonid
Abstract: Biomolecular transport systems based on cytoskeletal filaments and motor proteins have become promising tools for a wide range of nanotechnological applications. In this paper, we report control of such transport systems using substrates with switchable shape. We demonstrate this approach on the example of microtubules gliding on surfaces of self‐folding polymer bilayers with adsorbed kinesin motors. The polymer bilayers are able to undergo reversible transitions between flat and tube‐like shapes that allow the externally controlled retention and release of gliding microtubules. The demonstrated approach, based on surfaces with reconfigurable topography, opens broad perspectives to control biomolecular transport systems for bioanalytical and sensing applications, as well as for the construction of subcellular compartments in the field of synthetic biology. Abstract : Gliding around : A polymer bilayer is able to undergo reversible transitions between flat and tube‐like shapes, which allows the externally controlled retention and release of gliding microtubules. These findings open new possibilities to control biomolecular transport using substrates with switchable shapes.